Fast and Scalable Quantum Information Processing with Two‐Electron Atoms in Optical Tweezer Arrays (Adv. Quantum Technol. 3‐4/2019). Issue 3 (2nd April 2019) - Pagano, Guido; Scazza, Francesco; Foss‐Feig, Michael
Abstract : Neutral two‐electron atoms trapped in a programmable optical tweezer array can be locally manipulated by laser fields within a realistic and comprehensive experimental architecture for quantum information processing. The proposed scheme (see article number1800067 by Guido Pagano et al.) harnesses the nuclear spin and electronic clock degrees of freedom of alkaline‐earth‐like atoms to afford a fully controllable, robust and scalable quantum processor.